BR-163: from landless men to manless land - Passos, Messias Modesto dos [UNESP] (Univ Coimbra, Fac Letras, 2019)
In 1970, the Brazilian government started the project of building the large highways in the Amazon, highlighting the Transamazon, linking the region from East to West, and BR-163, known as Cuiaba-Santarem, from South to North - highways that crossed each other opened axes of penetration and integration. On the 16th of June, 1970, the Plan of National Integration (PIN) was created. The displacement of peasants from areas submitted to demographic pressure is made official and the speech of connecting the landless man of the Northeast to the manless land of the Amazon is put into practice in a chaotic and socially unfair way. In December 1974, the highway Cuiaba-Santarem was opened to the public. In Mato Grosso, the road would motivate the penetration of large agricultural projects and the colonization commanded by private groups. In the state of Para, in the stretch between Santarem and Ruropolis (at the crossing of Cuiaba-Santarem and Transamazon), the colonization directed to small landowners is predominant, commanded by the National Institute of Colonization and Land Reform (INCRA). Along all the road, the appreciation of the land, the attraction of migratory currents and the land speculation had immediate impacts to the local population - especially the indigenous ones. Our final consideration allow us, for the sake of concluding, to claim that the successive changes in the development plans according to the political and economic conjunctures, contributed to the failure of the great majority of colonization projects. Our conclusion is directed to some variables that points to the unsustainability of the regional development model: An excluding model: in the effort of choosing an image which is revealing of the environment of the present frontier I would say that it is of exclusion. A productivist model: after twenty year it is agribusiness that, notably in Mato Grosso, has the strongest development, supported by the necessity of Brazil obtaining income from exportable goods such as soybean. Deforesting and continuous fragmentation of Amazon forest.
Keywords: Amazon; BR-163; PIN; Indians; settlers